Fulfilling the Promise of Technology Transfer Fostering Innovation for the Benefit of Society - Hishida, Koichi (Springer Japan : Imprint: Springer, 2013)
Universities and research institutes are increasingly expected to contribute to society by creating innovation from the returns of their research results and the establishment of new technologies. Toward that goal, Keio University in Japan held an international symposium titled “Fulfilling the Promise of Technology Transfer: Fostering Innovation for the Benefit of Society.” From that symposium the following contents are included in the present volume: 1) A showcase of ideas and case studies to promote future creation of innovation by universities and research institutes worldwide, including information on the R&D value chain, licensing, income generation, start-ups and mechanisms to encourage entrepreneurship, and the changing role of universities in fostering innovation. 2) Introduction of active research projects that aim to productize successful research results on an international level. For example, the book includes results of research on stem cell technologies and regenerative medicine as well as the realization and application of polymer photonics and the development of the core technology of polymer photonics. 3) Case studies from the U.K. in developing industry–academia collaboration with various business partners ranging from start-ups and spinout companies to large enterprises. 4) Reports of the achievements of the technological transfer activities at Keio University supported by the 5-year public fund, with suggestions for future prospects.